INFLUENCE OF SCHOOL ENVIRONMENT, LEARNING INTERESTS ON PRODUCTIVE LEARNING OUTCOMES OF STUDENTS IN VOCATIONAL SCHOOLS, SOUTH JAKARTA - Hasanuddin (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2020)
This research aims to measure the school environment, and learning interest towards productive learning outcomes in accounting using survey methods. The population in this study is the vocational school of business management in the South Jakarta region, the outreach population is the vocational school 6 Jakarta, vocational school 18 Jakarta and vocational school 25 Jakarta, with a sample of 10 th grade accounting and financial institutions students totaling 178 students. The sampling technique uses proportional random sampling so that the sample is obtained by 123 students. Based on the results of the study concluded that the school environment and learning interest have a stimulant effect on learning outcomes. The school environment partially influences learning outcomes, while interest in learning partially does not affect learning outcomes.